A Discrete Tchebichef Transform Approximation for Image and Video Coding - Oliveira, Paulo A. M.; Cintra, Renato J.; Bayer, Fábio M.; Kulasekera, Sunera; Madanayake, Arjuna (IEEE signal processing letters, 2015)
In this letter, we introduce a low-complexity approximation for the discrete Tchebichef transform (DTT). The proposed forward and inverse transforms are multiplication-free and require a reduced number of additions and bit-shifting operations. Numerical compression simulations demonstrate the efficiency of the proposed transform for image and video coding. Furthermore, Xilinx Virtex-6 FPGA based hardware realization shows 44.9% reduction in dynamic power consumption and 64.7% lower area when compared to the literature.